The European Union, Nobel Peace Prize - Verdoy, SJ, Alfredo (Razón y fe, 2018)
After the first shock, no one has thrown up their hands in horror knowing that the European Union was awarded the Nobel Peace Prize by Norwegian Nobel Committee. Its vocation and its commitment to peace are in its DNA. Regardless its mistakes what it was and still is important is its effort for inclusion, its fight for practice and for respect human rights and for environment and its particular view of development which are not free of contradictions and they often become individual national interests. They were and will be more important than their mistakes. Europe and the rest of the world wouldn’t be what they are today without Europe Union.
Keywords: Europe Union; Nobel Peace Prize; ECSC; EEC; development; peace and progress